2013
DOI: 10.1021/ac303269w
|View full text |Cite
|
Sign up to set email alerts
|

Immobilized Nanorod Assemblies: Fabrication and Understanding of Large Area Surface-Enhanced Raman Spectroscopy Substrates

Abstract: We describe the fabrication of optimized plasmonic substrates in the form of immobilized nanorod assemblies (INRA) for surface-enhanced Raman spectroscopy (SERS). Included are high-resolution scanning electron micrograph (SEM) images of the surface structures, along with a mechanistic description of their growth. It is shown that, by varying the size of support microspheres, the surface plasmon resonance is tuned between 330 and 1840 nm. Notably, there are predicted optimal microsphere sizes for each of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
201
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(210 citation statements)
references
References 57 publications
9
201
0
Order By: Relevance
“…The main challenges associated with measuring the EF are accurate determination of the number of exiting molecules and reliable measurement of a weak normal Raman intensity under conditions of the laser power and accumulation time used in SERS measurements. From a practical point of view, the fundamental factor EF is often replaced by the analytical enhancement factor (AEF) [54,55], which is defined as the ratio between SERS and Raman intensities normalized to the corresponding analyte concentrations c SERS and c Raman or as the ratio between the analyte concentrations c Raman =c SERS that provide equivalent Raman and SERS intensities:…”
Section: Sers Response From Colloidal and Self-assembled Monolayersmentioning
confidence: 99%
“…The main challenges associated with measuring the EF are accurate determination of the number of exiting molecules and reliable measurement of a weak normal Raman intensity under conditions of the laser power and accumulation time used in SERS measurements. From a practical point of view, the fundamental factor EF is often replaced by the analytical enhancement factor (AEF) [54,55], which is defined as the ratio between SERS and Raman intensities normalized to the corresponding analyte concentrations c SERS and c Raman or as the ratio between the analyte concentrations c Raman =c SERS that provide equivalent Raman and SERS intensities:…”
Section: Sers Response From Colloidal and Self-assembled Monolayersmentioning
confidence: 99%
“…Consequently, a simpler approach utilizing an analytical enhancement factor (AEF) is commonly employed. At the same time, to illustrate versatility, the AEFs of Rh B and Na 3 AsO 4 were also calculated according to the following formula [27]:…”
Section: Surface-enhanced Raman Spectroscopymentioning
confidence: 99%
“…It was also demonstrated that the electromagnetic enhancement exponentially decays as the distance from the metal nanostructures increases. 29,30 This advantage made surface-enhanced Raman spectroscopy a widely used analytical approach for the detection and identification of various analytes, ranging from warfare agents to biomolecules. [31][32][33][34] Tip-enhanced Raman spectroscopy (TERS) combines the sensitivity of SERS and the precise spatial control of scanning probe microscopy (SPM) via a nanometer scale noble metal tip.…”
Section: Introductionmentioning
confidence: 99%